DOES ECONOMIC GROWTH, POPULATION GROWTH AND ENERGY USE IMPACT CARBON-DIOXIDE EMISSIONS IN PAKISTAN? AN ARDL APPROACH - LATIF, AHMAD; JAVED, RIMSHA (Bulletin of Business and Economics (BBE), 2021)
This study shows the impact of four major contributors GDP growth, Population growth, and Energy use on carbon-dioxide emissions in Pakistan. This research reviews a period of 46 years beginning from 1971 to 2017. Time series data is acquired for this purpose from WDI. The technique used here to determine the short run and long run impacts is ARDL. ADF approved the stationarity of data at a 5 % level of significance. ECM validates the co-integration among the variables. while CUSUM, CUSUMSQ, and RAMSEY RESET test displayed the stability and correct specification of the model. Therefore, empirically above-mentioned variables are statistically valid and render positive impact on CO2 excretion both in the transitory and at length regarding Pakistan.